"I'm Kind of a Feminist": Using Master Narratives to Analyze Gender Identity in Middle Childhood. Issue 1 (5th September 2018) - Rogers, Leoandra Onnie
Abstract : A robust literature documents the significance of gender in children's development, but gaps remain in understanding how developing gender identities link to gender inequalities. This article uses master narratives to analyze the ways that children's gender narratives reinforce or disrupt gender inequality. Semistructured interviews were conducted with 233 Black, White, mixed‐ and other‐race minority children (7–12 years old; M age  = 9.92; 61% girls) in racially diverse schools in the Pacific Northwest. Four narrative types were identified: two "master narratives" that reinforced gender inequality and two "alternative narratives" that disrupted it. Analyses revealed that 5th/6th‐graders (vs. 2nd–4th graders) and girls (vs. boys) were more likely to tell alternative narratives. The contributions of master narratives for understanding gender identity, development, and inequality are discussed.